2018
DOI: 10.1002/jez.2168
|View full text |Cite
|
Sign up to set email alerts
|

Light at night disrupts nocturnal rest and elevates glucocorticoids at cool color temperatures

Abstract: Nighttime light pollution is quickly becoming a pervasive, global concern. Since the invention and proliferation of light-emitting diodes (LED), it has become common for consumers to select from a range of color temperatures of light with varying spectra. Yet, the biological impacts of these different spectra on organisms remain unclear. We tested if nighttime illumination of LEDs, at two commercially available color temperatures (3000 and 5000 K) and at ecologically relevant illumination levels affected body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 54 publications
(83 reference statements)
2
34
0
Order By: Relevance
“…A major aim of our special issue was to reveal the multitude of molecular, physiological, and behavioral mechanisms that light pollution can affect. At the molecular and physiological level, these and previous papers have shown that ALAN can alter patterns of gene expression (Bedrosian, Galan, Vaughn, Weil, & Nelson, 2013;Dominoni et al, 2018;Fonken & Nelson, 2014;Shuboni & Yan, 2010), hormone secretion (Alaasam et al, 2018;de Jong et al, 2016;Dominoni, Goymann, Helm, & Partecke, 2013;Ouyang, Davies, & Dominoni, 2018), body temperature (Kumar et al, 2018), energy expenditure (Welbers et al, 2017), immune function (Bedrosian, Fonken, Walton, & Nelson, 2011;Cissé, Russart, & Nelson, 2017;Fonken, Lieberman, Weil, & Nelson, 2013), and oxidative stress (McLay et al, 2018;Navara & Nelson, 2007). Given, such extensive changes in the underlying physiology, it comes with no surprise that an impressive array of behavioral effects of ALAN have been shown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 87%
“…A major aim of our special issue was to reveal the multitude of molecular, physiological, and behavioral mechanisms that light pollution can affect. At the molecular and physiological level, these and previous papers have shown that ALAN can alter patterns of gene expression (Bedrosian, Galan, Vaughn, Weil, & Nelson, 2013;Dominoni et al, 2018;Fonken & Nelson, 2014;Shuboni & Yan, 2010), hormone secretion (Alaasam et al, 2018;de Jong et al, 2016;Dominoni, Goymann, Helm, & Partecke, 2013;Ouyang, Davies, & Dominoni, 2018), body temperature (Kumar et al, 2018), energy expenditure (Welbers et al, 2017), immune function (Bedrosian, Fonken, Walton, & Nelson, 2011;Cissé, Russart, & Nelson, 2017;Fonken, Lieberman, Weil, & Nelson, 2013), and oxidative stress (McLay et al, 2018;Navara & Nelson, 2007). Given, such extensive changes in the underlying physiology, it comes with no surprise that an impressive array of behavioral effects of ALAN have been shown.…”
Section: The Effects Of Alan At Different Levels Of Biological Orgamentioning
confidence: 87%
“…Furthermore, reduced food abundance was demonstrated to be associated with increased 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 Artificial light at night harms budgerigars corticosterone levels and decreased reproductive performance in the common murre, Uria aalge (Kitaysky et al 2007). In birds and mice, it has been demonstrated that ALAN exposure can provoke elaborated stress responses, as evidenced by an increase in stress hormones such as corticosterone (Ouyang et al 2015;Alaasam et al 2018;Zubidat et al 2018). Finally, chronic noise, as another pervasive anthropological environmental pollution, can also trigger stress responses in western bluebirds (Sialia mexicanan) and, consequently, increase body mass and decrease egg hatchability…”
Section: Discussionmentioning
confidence: 99%
“…In great tits (Parus major), dim ALAN applied either in December or February decreased sleep duration and advanced activity onset by approximately 24 min compared with unexposed birds . In zebra finches (Taeniopygia guttata), 5000 K LED ALAN increased both activity and corticosterone levels compared with either 3000 K illumination or control "natural" conditions (Alaasam et al 2018). Significant associations between ALAN exposure and early occurrence of seasonal dawn and dusk singing have been also reported in different songbird species (Da Silva et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Melanopsin, pinopsin and vertebrate ancient opsin were all highly stimulated by the four light sources while neuropsin was marginally stimulated. These findings are the first to test how different non‐visual photoreceptors are stimulated by numerous anthropogenic light sources and reveal that numerous organisms are at risk for changes to circadian rhythms, seasonal reproduction, hormone cascades and immune function, phenology and migration (Kuenzel et al ., ; Gaston et al ., ; Alaasam et al ., ). We must emphasize that previous research has repeatedly shown that these non‐visual photoreceptors are directly responsible for changes in reproduction, physiology, immunity and phenology (Gaston et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Organisms are chronically exposed to artificial lighting, which affects foraging, communication, circadian rhythms, endocrinology, predator-prey interactions, reproduction and other biological functions (Longcore, 2010; Dominoni et al, 2013;Br€ uning et al, 2015). Ultimately, these changes in animal behavior, physiology and ecology from artificial light at night are due to organismal reception of anthropogenically produced light (Kuenzel, Kang & Zhou, 2014;Alaasam et al, 2018). Millions of different species of organisms have evolved the ability to detect light for visual tasks and as cues for circadian rhythms and phenology, thus altering natural light conditions has grave ecological consequences (Cronin et al, 2014;Garc ıa-Fern andez et al, 2015;Davies & Smyth, 2017;Gaston et al, 2017).…”
Section: Introductionmentioning
confidence: 99%